Edukasi Kebutuhan Gizi Remaja Putri di Dayah Terpadu Al Madinatuddiniyah Syamsuddhuha Kecamatan Dewantara Kabupaten Aceh - Rosyita Rosyita; Elizar Elizar; Hendrika Wijaya Kartini Putri; Jasmiati Jasmiati (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Adolescent girls are very vulnerable to malnutrition. They need protein, iron, and other micronutrients to support accelerated adolescent growth and meet the increased iron needs during menstruation. Women are more likely to suffer from malnutrition than men, for reasons including women's reproductive biology, low social status, poverty, and lack of education. Sociocultural traditions and disparities in domestic work patterns can also increase women's chances of malnutrition. The problem-solving method used is educating through presentations on the nutritional needs of young women by distributing leaflets and posters containing the nutritional needs of adolescents and their problems. During the community service activities, 30 young women attended. Community service activities carried out for two days at Dayah Terpadu Al Madinatuddiniyah Syamsuddhuha, Dewantara District, North Aceh Regency, there was an increase in the average knowledge of the target audience of community service about education for fulfilling nutritious meals for young women, in the pretest evaluation the target audience had an average knowledge of 70 ,3 and on the posttest evaluation the average value became 84.7. It is important for health workers to continue to provide information about the nutritional needs of adolescents as an effort to increase adolescent knowledge by involving teachers in the dayah as the closest environment for adolescents.